Work Engagement: Investigating the Role of Transformational Leadership, Job Resources, and Recovery. Issue 6 (18th August 2017) - Hawkes, Amy J.; Biggs, Amanda; Hegerty, Erin
ABSTRACT: While the relationship between job resources and engagement has been well established, a greater understanding of the upstream factors that shape job resources is required to develop strategies to promote work engagement. The current study addresses this need by exploring transformational leadership as an upstream job resource, and the moderating role of recovery experiences. It was hypothesized that job resources would mediate the relationship between transformational leadership and engagement. Recovery experiences were expected to moderate the relationship between resources and engagement. A sample of 277 employees from a variety of organizations and industries was obtained. Analysis showed direct relationships between: transformational leadership and engagement, and transformational leadership and job resources. Mediation analysis using bootstrapping found a significant indirect path between transformational leadership and engagement via job resources. Recovery experiences did not significantly moderate the relationship between job resources and engagement. To date, the majority of published literature on recovery has focused on job demands; hence the nonsignificant result offers insight of a potentially more complex relationship for recovery with resources and engagement. Overall, the current study extends the JD-R model and provides evidence for broadening the model to include upstream organizational variables such as transformational leadership.